Adaptive phase-field modeling of dynamic brittle fracture in composite materials. (15th February 2023) - Li, Weidong; Nguyen-Thanh, Nhon; Du, Hejun; Zhou, Kun
Abstract: An adaptive phase-field modeling approach is developed for the dynamic brittle fracture of composite materials subjected to impact loading. This approach is capable of capturing the dynamic fracture patterns in composite materials including matrix cracking, delamination between adjacent plies, and interaction between the two failure modes via the exploitation of interface and crack phase fields. The driving force for the crack evolution is derived by introducing the contributions of the longitudinal and transverse damage considering the tension–compression asymmetry. Moreover, an anisotropic crack surface density function is introduced by considering the material anisotropy induced by fibers. The computational efficiency of the dynamic fracture modeling is improved via the adaptive mesh refinement strategy within the framework of the isogeometric-meshfree approach. The Newmark implicit integration scheme is used for the temporal discretization of the phase-field governing equations. Finally, simulations of both mode-I and mixed-mode fracture, such as the dynamic branching and the three-point bending tests, are implemented for homogeneous materials and composites, which demonstrates the reliability of the developed approach.